A Novel Calculator for Estimating Prostate Volume in Daily Urology Services - Lim, Jasmine; Rampal, Sanjay; Razack, Azad Hassan Abdul; Malek, Rohan; Sundram, Murali; Nasuha, Noor Azam; Ooi, Chong Chien; Ong, Teng Aik; Sothilingam, Selvalingam (Elsevier, 2018)
Objectives: To develop a simple prostate volume (PV) calculator that can aid in managing patients with lower urinary tract symptoms (LUTS) secondary to benign prostatic enlargement at daily urology services in developing Asian countries. Materials and Methods: We conducted a cross-sectional study of men aged above 40 years with no history of prostate cancer, prostate surgery, or 5α-reductase inhibitor treatment. Serum prostate-specific antigen (PSA) and total PV were measured in each subject. Potential sociodemographic and clinical variables including age, weight, comorbidities, and International Prostate Symptom Score (IPSS) were collected. Of 1034 subjects, 837 were used in building the PV calculator using regression analysis. The remaining 1/5 (n = 197) was used for model validation. Results: There were 1034 multiethnic Asian men (Chinese 52.9%, Malay 35.4%, and Indian 11.7%) with mean age of 60 ± 7.6 years. Average PV was 29.4 ± 13.0 mL while the overall mean of PSA was 1.7 ± 1.7 ng/mL. We identified age, IPSS, weight, and PSA (all P <.05) in the PV regression model. Using the validation set, the coefficient of determination (R2) of this PV calculator was 0.47 where PV = 20.6 + (age − 60) × 0.1 + (IPSS score) × 0.1 + (Weight − 70) × 0.3 + (history of alpha-blocker treatment for LUTS) × 9.6 + PSA × 3.7. The area under curve of this model in predicting PV above 30 mL and 40 mL were 0.82 (95% confidence interval, 0.75-0.88) and 0.91 (95% confidence interval, 0.87-0.96), respectively. Conclusion: We develop a PV calculator that is simple and accurate to be used in routine clinical consultation for patients with LUTS. A separate study is important to confirm and to validate the findings in other populations.